Education in Serbia as Founding Principle of the Local Economic Development - Hajnalka Kovács Sárkány; Vilmos Kovács (DETUROPE)
The aspiration of Serbia to join the European Union requires the transformation of the educational system of the country to adapt EU mechanisms. Such endeavours are reflected in the Law on Higher Education modificated in July 2013 and Law on Adult Education, wich is published in 2014. These may infer social and economic consequences on a wide scale. Our intention was to present the structure of the Serbian education system and the distribution of the educational level of the population applying secondary data analysis in our study. Furthermore, our goal was to shed light on a particular section of the Law on Higher Education which regulates the recognition of foreign degree (diploma); in addition, we intended to touch upon the issue of trainings in non-formal education controlled by the Law on Adult Education. Lastly, we addressed changes in the unemployment rate and levels of qualification of those without a job. Our work is applied from the perspectives of knowledge and knowledge transfer; since local economic development depends highly on the accumulated pieces of information acquired by experts.